Rehabilitation for torture survivors: Six evidence myths and their implications for future research - Patel, Nimisha; Williams, Amanda (Torture Journal, 2022)
Whilst it is established that torture survivors suffer from complex, multiple and often severe and enduring physical, psychological, social, welfare and many other difficulties; and that rehabilitation as reparation should be holistic, interdisciplinary and specialist, majority of the research on rehabilitation focuses increasingly and almost exclusively on psychological interventions. Further, assumptions that this research provides evidence of which are effective psychological interventions may underpin and skew services funded and provided to torture survivors. In this paper we challenge some of those assumptions, and discuss the conceptual, theoretical, epistemological and methodological limitations of this research and implications for future research.